(untitled) (Bangladesh Journal of Pharmacology, 2015)
A series of novel thiazolidinedione analogues (TZD) were designed and synthesized potent inhibitors of HBV capsid assembly. The synthesis of thiazolidine-2,4-dione derivatives (4a4o), starting from the condensation of 5-(ethoxymethylene)thiazolidine-2,4-dione (1) with various secondary amines (3) derived from biologically active compounds. The newly synthesized TZD analogues 4a-4o were characterized by 1H NMR, 13C NMR, and MS and evaluated for their anti-HBV activity. Most of the compounds inhibited the expression of viral antigens at low concentration. Six compounds, 4g, 4h, 4l, 4m, 4n, and 4o, demonstrated potent inhibition of HBV DNA replication at submicromolar range. Of these five initial hits, compound 4o was the most active when compared with lamivudine.